Modern Trends in Hypercomplex Analysis - Bernstein, Swanhild; Kähler, Uwe; Sabadini, Irene; Sommen, Franciscus (Trends in Mathematics, 2016)
This book contains a selection of papers presented at the session "Quaternionic and Clifford Analysis" at the 10th ISAAC Congress held in Macau in August 2015. The covered topics represent the state-of-the-art as well as new trends in hypercomplex analysis and its applications.